Evaluating the wound healing activity of fabricated stingless bee honey hydrogels in an animal model - Abd Jalil, Mohd Azri; Md Isa, Muhammad Lokman; Azhan, Umar; Khalid, Kamarul Ariffin; Barkat, Md. Abul; Ab. Hadi, Hazrina (IIUM Press, 2025)
Introduction: Honey is a well-established treatment for wound healing and had been used for ages. However, there are limitations when it is directly applied to the wound such as inconsistent dosage and pain during dressing changes. The incorporation of honey into hydrogel could overcome these problems. The study is aimed at developing a suitable honey-based hydrogel formulation for wound healing application by using systematic experimental design from response surface methods (RSM). Methods: The hydrogel’s base was made from polyvinyl alcohol (PVA), polyethylene glycol (PEG), glycerol and agar. A two-level factorial design was selected to screen the factors followed by centred composite design for optimization. The characterizations of the optimized formulation were observed in term of hydrophilicity and rheological. The optimized formulation was further assessed in an in vivo wound healing study in New Zealand albino rabbits. Results: PEG and agar concentration was found to be the most important process variable based on the screening result. The optimised hydrogel has a good hydrophilicity ability and rheological property. In in vivo healing study, the healing in the honey incorporated hydrogel treated group was significantly faster than the no treatment group, as demonstrated in wound closure percentage and histological assessment. From the results, the wound in the honey hydrogel treatment group has entered the remodelling phase compared with the control group that was still in the proliferation phase. Conclusion: Based on all of these results, stingless bee honey incorporated hydrogel has a promising application as an efficient wound dressing